What is the preferred geometry of sulfur–disulfide interactions?. Issue 43 (25th March 2020) - Veljković, Ivana S.; Veljković, Dušan Ž.; Sarić, Gordana G.; Stanković, Ivana M.; Zarić, Snežana D.
Abstract : Combined crystallographic and quantum chemical studies showed that in most cases, in crystal structures, interactions between sulphur atoms and disulphide bonds are bifurcated. Abstract : Non-covalent interactions between disulfide fragments and sulfur atoms were studied in crystal structures of small molecules and by quantum chemical calculations. Statistical analysis of the geometrical data from the Cambridge Structural Database (CSD) reveals that in most cases, interactions between sulfur and disulfide bonds are bifurcated. Quantum chemical calculations are in agreement with those findings. A strong interaction energy was calculated for bifurcated interactions ( E CCSD(T)/CBS = −2.83 kcal mol −1 ) considering the region along the disulfide bond. Non-bifurcated interactions are weaker except in cases where σ-hole interaction is possible or in cases where S⋯S interaction is accompanied by additional hydrogen bonds ( E CCSD(T)/CBS = −3.26 kcal mol −1 ). SAPT decomposition analysis shows that dispersion is the main attractive force in the studied systems while electrostatics plays a crucial role in defining the geometry of interactions.